Toleransi Beragama Pada Anak Usia Dini: Implementasi dan Strategi Guru di TK PGRI 88 Semarang - Rahayu Nila Fadlilah; Mursid (Institut Agama Islam Negeri Madura, 2024)
This research aims to identify and analyze the implementation and strategies for teaching religious tolerance to early childhood students at TK PGRI 88 Semarang, an educational institution in a suburban environment designed to support character education in the context of religious diversity. A qualitative field method was employed, with data collection through observation, interviews, and document analysis. The results show that TK PGRI 88 Semarang has successfully created an educational environment conducive to developing tolerant attitudes in young children through inclusive facilities and a holistic learning approach. Teachers at this school implement strategies such as the use of stories, songs, and games, as well as interfaith activities integrated into the children's daily routines. Active involvement of parents and the community also plays a crucial role in reinforcing the values of tolerance taught at school. The conclusion of this study is that religious tolerance education for early childhood at TK PGRI 88 Semarang represents an important step in shaping an inclusive generation that appreciates diversity, relevant to the needs of Indonesia's multicultural society. The findings of this research contribute significantly to understanding the practices of religious tolerance education and offer recommendations for further development in similar educational institutions.